2015
DOI: 10.1071/fp14166
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient leaf transpiration and nonstructural carbohydrates are beneficial for high-temperature tolerance in three rice (Oryza sativa) cultivars and two nitrogen treatments

Abstract: To determine whether variations in high-temperature (HT) tolerance in three rice (Oryza sativa L.) cultivars and two N treatments are related to leaf transpiration rate (E), and whether the involvement of nonstructural carbohydrates (NSC) in HT tolerance is related to E, a pot experiment supplied with two N levels (low N, 0.077 g urea kg–1 soil; sufficient N, 0.538 g urea kg–1 soil) was conducted under ambient temperature (AT) and HT with three cultivars, N22, Zhenshan 97B and Koshihikari. HT significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
4
29
0
1
Order By: Relevance
“…This would lead to higher rates of E in the mutants, despite lower rates of g s . In our previous study, higher transpiration rate is beneficial for high-temperature tolerance in rice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This would lead to higher rates of E in the mutants, despite lower rates of g s . In our previous study, higher transpiration rate is beneficial for high-temperature tolerance in rice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because grain yield capacity sustains on carbohydrate partitioning, assimilate remobilization from stems and leaf sheaths becomes crucial in exigency, when challenging environments slacken current photosynthesis. NSC re-translocation associates with stress tolerance such as high or low irradiance ( Okawa et al, 2003 ), water deficiency stress ( Yang et al, 2001a ; Gupta et al, 2011 ), heat stress ( Tahir and Nakata, 2005 ; Morita and Nakano, 2011 ; Shi et al, 2013 ; Xiong et al, 2015 ) and low nitrogen availability ( Pan et al, 2011 ). These results illustrate the importance of stem NSC for yield stability and stress resistance in cereal crops.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, a canopy-temperature-based irrigation scheduling procedure (Wanjura & upchurch, 1997) may contribute to the reduction of heat damage in rice. In addition, it has been indicated that the use of nitrogen application with a heat-tolerant variety is a highly effective means of decreasing heat damage via lowering of the canopy temperature by enhancing evapotranspiration (Xiong et al, 2015). Also, it would be effective to use varieties which have a higher transpiration conductance and/or lower temperature of flowering rice panicle (Fukuoka et al, 2012;Maruyama et al, 2013) for diminishing heat damage.…”
Section: Crop Model Approachmentioning
confidence: 99%